The forgotten learning disability: epidemiology of written-language disorder in a population-based birth cohort (1976-1982), Rochester, Minnesota - Katusic, Slavica K; Colligan, Robert C; Weaver, Amy L; Barbaresi, William J (Pediatrics (Evanston), 2009)
The aim of this study was to report the incidence rates and other epidemiologic characterizations of written-language disorder. There have been no epidemiologic studies on the incidence of written-language disorder in the United States, and the use of a population-based birth cohort, longitudinally followed, is the most powerful method for reaching this objective. In this population-based, retrospective birth cohort study, subjects included 5718 children born between 1976 and 1982 in Rochester, Minnesota, who remained in the community after 5 years of age. Records from all public and nonpublic schools, medical facilities, and private tutorial services were reviewed and results of all individually administered IQ and achievement tests, and extensive medical, educational, and socioeconomic information, were collected. The essential features of writing problems from the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision were included in our operationalized definition of written-language disorder. Written-language disorder incident cases were established by using research criteria based on 3 formulas (regression-based discrepancy, nonregression-based discrepancy, and low achievement). Cumulative incidence rates of written-language disorder varied from 6.9% to 14.7% depending on the formula. Boys were 2 to 3 times more likely to be affected than girls regardless of the formula. Among all written-language disorder cases (N = 806), 25% (n = 203) had written-language disorder without a reading disability. Specifics of the writing problems were identified for 87% (n = 702) of written-language disorder cases. In this population-based birth cohort of school-aged children, written-language disorder was at least as frequent as reading disabilities and significantly more frequent among boys than girls.